Impact of drug use policy on the appropriate use of direct acting antiviral agents for Hepatitis C in Saudi Arabia - Ahmed Saqer Alotaibi; Nour Shamas; Umair Uddin Ansari; Faisal M Sanai; Ali Alshahrani; Ahmed Ibrahim Fathelrahman; Mohammed Ali Aseeri (Wolters Kluwer Medknow Publications, 2021)
Background: Ministry of National Guard-Health Affairs in Saudi Arabia developed a new policy for the use of direct antiviral agents (DAAs) for hepatitis C. The present study was conducted to evaluate prescribers' compliance and the impact of the policy on DAAs appropriate use. Materials and Methods: This study was conducted at King Abdul Aziz Medical City in Jeddah, Saudi Arabia. The study compares patients' data during 1 year before and 1 year after policy initiation. The primary outcomes were compliance to monitoring parameters, appropriateness of treatment and treatment eligibility. Secondary outcomes included sustained virologic response at 12 weeks, documentation of potential drug-drug interactions and treatment costs. Independent samples t-test and Chi-square test were used when applicable. A P < 0.05 was considered statistically significant. Results: One hundred and three patients were included in analysis (46 before and 57 after policy). Prescriber compliance to baseline monitoring parameters was 67.4% before policy and 82.5% after-policy (P = 0.076). International normalized ratio (INR) was requested in 84.8% of cases before policy compared to 96.5% after-policy (P = 0.036). Treatment options offered to patients were appropriate in 52.2% of cases before policy and in 82.5% after-policy (P = 0.001). Conclusion: There is a significant improvement in the baseline monitoring of INR. Treatment options offered after policy implementation were significantly more appropriate.